Repeated Partnership Games with Imperfect Monitoring and No Discounting - Radner, Roy (Review of Economic Studies, 1986)
In a partnership game, each player's utility depends on the other players' actions through a commonly observed consequence (e.g. output, profit, price), which is itself a function of the players' actions and an exogenous stochastic environment. If a partnership game is repeated infinitely, and each player's payoff in the infinite game (supergame) is the long-run average of his expected one-period utilities, then efficient combinations of one-period actions can be sustained as Nash equilibria of the supergame even if the players cannot observe other players' actions or information, but can only observe the resulting consequences.